Surfactants effects on enhancing electrical performance of nanoparticle-based mineral transformer oil - Kadim, Emran Jawad; Ahmad Noorden, Zulkarnain; Adzis, Zuraimy; Azis, Norhafiz; Mohamad, Nur Aqilah (IEEE, 2023)
Introducing nanoparticles to enhance the performance of mineral transformer oil has been con- sidered in many studies recently. Typically, researchers focused on the use of widespread types of nanoparticles such as aluminum oxide, silicon dioxide, and titanium dioxide. However, there is no consensus on which type or concentration is suitable for this application. In this article, we studied different types of nanoparticles to inves- tigate their effects on the electrical performance of mineral transformer oil with and without the use of surfactants. Design-of-experiments (DOE) approach was adopted to systematically produce oil-based nanoparticles, referred to as nanofluids, under different concentrations of nanopar- ticles and surfactants. With three concentration levels of three nanoparticles, namely, zinc iron oxide (ZnFe2O4), titanium carbide (TiC), and molybdenum dioxide (MoO3), the nanofluids were produced with three types of surfac- tants, which were oleic acid (OA), cetyl trimethyl ammonium bromide (CTAB), and polyvinyl alcohol (PA) under three different concentrations. Fifty successive ac breakdown voltage (BDV) tests were carried out for each sample using mushroom–mushroom cell according to IEC 60156. The results showed the dominance of TiC for two samples with and without surfactants. In addition, the DOE results showed the importance of concentration of nanoparticles and their types to enhance mineral oil’s performance.